1992
DOI: 10.1016/0014-5793(92)80785-f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pancreatic type phospholipase A2 on isolated porcine cerebral arteries via its specific binding sites

Abstract: The addition of porcine pncrcatir voup I phorpholipsc A: WA:-I) produced Y lranricnt contrastion followcd by n rclmxation in hslisal strips of prcinc ccrcbrul artcries. Its ED, value (2.3 RM) was almosf idcntir;ll10 the t& veluct3.9 nM) calculated from lhc spcrinc binding of 'zslWxlsd porcine PLA:-t in cultured porcine cerebral arterial smoolh murlc ccllr. Typcapscific action of PLAIs and homologousdcxnritization rlrongly impliratcd the involvcmcnt of PLA+sprcific sitar in the rcsponfe. The tnnrlcnt contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 11 publications
0
23
0
3
Order By: Relevance
“…[35][36][37] The correlation between sPLA 2 -IIA levels and disease status has led to the development of pharmacological agents that are capable of inhibiting sPLA 2 -IIA and possibly the activities of other sPLA 2 , which would be expected to be beneficial for the mitigation of disease. As a result of our ongoing efforts to develop new sPLA 2 inhibitors from natural products using an activity-guided isolation procedure, we isolated a new human sPLA 2 -IIA and -V inhibitor, papyriflavonol A, from B. papyrifera.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] The correlation between sPLA 2 -IIA levels and disease status has led to the development of pharmacological agents that are capable of inhibiting sPLA 2 -IIA and possibly the activities of other sPLA 2 , which would be expected to be beneficial for the mitigation of disease. As a result of our ongoing efforts to develop new sPLA 2 inhibitors from natural products using an activity-guided isolation procedure, we isolated a new human sPLA 2 -IIA and -V inhibitor, papyriflavonol A, from B. papyrifera.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that sPLA 2 -IB can elicit various biological responses possibly via PLA 2 R binding, such as proliferation and chemokinetic migration of vascular smooth muscle cells and potent vasoactive actions in cerebral arteries (17,38). In addition, we have recently demonstrated that sPLA 2 -X elicits marked release of arachidonic acid leading to lipid mediator productions in various cell types, including monocytes/ macrophages (15,16,39).…”
Section: Discussionmentioning
confidence: 99%
“…The pancreatic sPLA 2 has long been thought to act only as a digestive enzyme (8). However, the presence of this sPLA 2 in several non-digestive tissues has been demonstrated (9 -11), and it is now thought to play a role in airway and vascular smooth muscle contraction (12,13) as well as in cell proliferation (14). The inflammatory sPLA 2 has been purified and cloned from several sources (15,16) and is believed to play a central role in inflammatory processes (reviewed in Refs.…”
Section: Receptor Essentially Via Crds 3-6mentioning
confidence: 99%